A novel approach to mapping the atrial ganglionated plexus network by generating a distribution probability atlas - Kim,M-Y; Sikkel,MB; Hunter,RJ; Haywood,GA; Tomlinson,DR; Tayebjee,MH; Ali,R; Cantwell,CD; Gonna,H; Sandler,B; Limb,E; Furniss,G; et al. (Journal of Cardiovascular Electrophysiology, 2018)
INTRODUCTION: The ganglionated plexuses (GPs) of the intrinsic cardiac autonomic system are implicated in arrhythmogenesis. GP localization by stimulation of the epicardial fat pads to produce atrioventricular dissociating (AVD) effects is well described. We determined the anatomical distribution of the left atrial GPs that influence AV dissociation. METHODS AND RESULTS: High frequency stimulation was delivered through a Smart-Touch™ catheter in the left atrium of patients undergoing atrial fibrillation (AF) ablation. 3D locations of points tested throughout the entire chamber were recorded on the CARTO™ system. Impact on the AV conduction was categorized as ventricular asystole, bradycardia or no effect. CARTO™ maps were exported, registered and transformed onto a reference left atrial geometry using a custom software, enabling data from multiple patients to be overlaid. In 28 patients, 2108 locations were tested and 283 sites (13%) demonstrated atrioventricular dissociation effects (AVD-GP). There were 10 AVD-GPs (IQR 11.5) per patient. 80% (226) produced asystole and 20% (57) showed bradycardia. The distribution of the two groups were very similar. Highest probability of AVD-GPs (>20%) were identified in: infero-septal portion (41%) and right inferior pulmonary vein base (30%) of the posterior wall, right superior pulmonary vein antrum (31%). CONCLUSION: It is feasible to map the entire left atrium for AVD-GPs prior to AF ablation. Aggregated data from multiple patients, producing a distribution probability atlas of AVD-GPs, identified three regions with a higher likelihood for finding AVD-GPs and these matched the histological descriptions. This approach could be used to better characterise the autonomic network. This article is protected by copyright. All rights reserved.